Heterogeneity of HLA-G Expression in Cancers: Facing the Challenges - Lin, Aifen; Yan, Wei-Hua (Frontiers in Immunology, 2018)
Phenotypic heterogeneity has been observed in most malignancies, which represents a considerable challenge for tumour therapy. In recent decades, the biological function and clinical significance of the human leukocyte antigen (HLA)-G have been intensively explored. It is now widely accepted that HLA-G is a critical marker of immunotolerance in cancer cell immune evasion and is strongly associated with disease progress and prognosis for cancer patients. Moreover, it has recently been emphasized that the signalling pathway linking HLA-G and immunoglobulin-like transcripts (ILTs) is considered an immune checkpoint. In addition, HLA-G itself can generate at least seven distinct isoforms, and intertumour and intratumour heterogeneity of HLA-G expression is common across different tumour types. Furthermore, HLA-G heterogeneity in cancers has been related to disease stage and outcomes, metastatic status and response to different therapies. This review focuses on the heterogeneity of HLA-G expression in malignant lesions, and clinical implications of this heterogeneity that might be relevant to personalized treatments are also discussed.